A Simple Graphical Method to Determine the Order in Catalyst. (8th January 2016) - Burés, Jordi
Abstract: A graphical analysis to elucidate the order in catalyst is presented. This analysis uses a normalized time scale, t  [cat]T n, to adjust entire reaction profiles constructed with concentration data. The method is fast and simple to perform because it directly uses the concentration data, therefore avoiding the data handling that is usually required to extract rates. Compared to methods that use rates, the normalized time scale analysis requires fewer experiments and minimizes the effects of experimental errors by using information on the entire reaction profile.